2008
DOI: 10.1128/jvi.02356-07
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Constraints Limit Options for Cytotoxic T-Lymphocyte Escape in the Immunodominant HLA-B27-Restricted Epitope in Human Immunodeficiency Virus Type 1 Capsid

Abstract: Control of human immunodeficiency virus type 1 (HIV-1) by HLA-B27-positive subjects has been linked to an immunodominant CD8؉ cytotoxic T-lymphocyte (CTL) response targeting the conserved KK10 epitope (KRWIILGLNK 263-272 ) in p24/Gag. Viral escape in KK10 typically occurs through development of an R 264 K substitution in conjunction with the upstream compensatory mutation S 173 A, and the difficulty of the virus to escape from the immune response against the KK10 epitope until late in infection has been associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
169
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 140 publications
(181 citation statements)
references
References 63 publications
10
169
1
1
Order By: Relevance
“…Gag protein was chosen because CTL responses to Gag, particularly to its proteolytic processing product p24 Gag , have been associated with better control of HIV viremia (19,23,(26)(27)(28)(29)(30)(31). Similarly, a direct correlation between Gag-specific T cell responses prior to infection and control of acute viremia was found in DNA-vaccinated macaques (32).…”
mentioning
confidence: 94%
“…Gag protein was chosen because CTL responses to Gag, particularly to its proteolytic processing product p24 Gag , have been associated with better control of HIV viremia (19,23,(26)(27)(28)(29)(30)(31). Similarly, a direct correlation between Gag-specific T cell responses prior to infection and control of acute viremia was found in DNA-vaccinated macaques (32).…”
mentioning
confidence: 94%
“…First, during HIV and hepatitis C virus (HCV) infections, viral escape from HLA-B27-restricted cytotoxic T cells targeting immunodominant epitopes is undoubtedly a difficult process. It usually requires multiple compensatory mutations to counterbalance structural and functional constraints having a high cost for the viral fitness [48,52,53]. Secondly, a number of immunological benefits of the virus-specific, HLA-B27-restricted CD8…”
Section: Hla-b27 a Molecule With Two Faces: Protection From Viral Inmentioning
confidence: 99%
“…These double mutants would take longer to arise than single beneficial mutants. Fitness interactions of this type, more generally known as fitness epistasis, are common and strong in HIV-1 in the context of its adaptation to an alternative host-cell coreceptor (Da Silva et al 2010) and have been reported for the evolution of escape mutants in response to CD8 + T cell selection (Yeh et al 2006;Schneidewind et al 2008).…”
Section: Discussionmentioning
confidence: 99%